PASSENGER CAR EQUIVALENT AT SIGNALIZED INTERSECTIONS WITH COUNTDOWN TIMER IN MALANG CITY - Anggoro, Dikka; Sulistio, Harnen; Wicaksono, Achmad; Sulistyono, Sonya (Universitas Jember, 2018)
Passenger car equivalents (PCE) is used in highway capacity analysis to convert a mixed vehicle flow into an equvalent passenger car flow. PCE value for a vehicle is not constant but varies with traffic and roadway conditions arround. In this study, PCE for motorcycle, light vehicle and heavy vehicle were developed at signalized intersection on saturation condition with and without countdown timer (CDT) in Malang City and to evaluate the value of analysis pcu and MKJI 1997 pcu. PCE data were collected at five intersection; Ciliwung, Dieng, BCA, L.A. Sucipto and Rampal intersection. A digital video camera was utilized for data collection and linier regresion method was used to calculate the PCE values. The analysis result shows for the average pcu value for the type of motorcycle (MC) at countdown timer on and off condition is 0,294 and 0,293. As for the types of heavy vehicles (HV) at countdown timer on and off conditions are 1.565 and 1.507. While to evaluate the pcu value, there is a significant difference between the value of pcu analysis results with the value of MKJI 1997 with a level of confidence in the significance of 95%. For percentage of motorcylce type (MC) if the percentage value of 75% the pcu value will increase. While for heavy vehicle type (HV) if the percentage is above 1.5% then the value of emp will increase because HV type has big dimension. Ekivalensi mobil penumpang (emp) digunakan untuk analisis kapasitas jalan. Nilai emp untuk kendaraan tidaklah konstan atau sama tetapi memiliki nilai yang bervariasi. Pada penelitian ini mencari nilai emp untuk jenis kendaraan sepeda motor (MC) dan kendaraan berat (HV) pada simpang bersinyal pada kondisi jenuh dengan menggunakan countdown timer (CDT) pada kondisi on dan off. Data nilai emp dikumpulkan pada lima simpang di Kota Malang; Simpang Ciliwung, Dieng, BCA, L.A. Sucipto dan Rampal. Video kamera digunakan untuk merekam dan pengumpulan data dan untuk menghitung nilai emp menggunakan metode regresi linier. Hasil yang diperoleh menunjukan bahwa nilai rata-rata untuk sepeda motor pada kondisi CDT on dan off ialah 0,294 dan 0,293. Sedangkan untuk kendaraan berat (HV) untuk kondisi CDT on dan off ialah 1,565 dan 1,507. Sedangkan untuk evaluasi nilai emp terdapat perbedaan yang signifikan diantara nilai emp hasil analisis dengan nilai emp MKJI 1997 dengan tingkat kepercayaan sebesar 95%. Untuk persentase jenis MC, apabila persen kendaraan bermotor meningkat sebesar 75% maka nilai empnya akan meningkat. Sedangkan untuk HV, apabila persen kendaraan berat (HV) meningkat sebesar 1,5% maka nilai empnya akan meningkat dikarenakan dimensi yang besar.